The usefulness of 3D-CT simulation and intraoperative navigation in pediatric minimally invasive surgery - Keigo Yada; Hiroki Mori; Hiroki Ishibashi (Elsevier, 2018)
Background/aims: The aim of this study was to evaluate the usefulness of 3D-CT simulation in pediatric minimally invasive surgery. Methodology: adenomatoidPreoperative 3D-CT simulation was performed using data from contrast enhancement MDCT and SYNAPSE VINCENT software. The images of 3D CT simulation were installed to iPad, and were used as intra-operative images. From 2011 to 2015, three cases who underwent minimally invasive surgery were enrolled. (hepatoblastoma (n = 1), Congenital cystic aednomatoid malformation (CCAM) (n = 1) and mediastinal tumor (n = 1)). Results: Case 1: 1y-6m male with hepatoblastoma (PRETEXT I, S5) underwent laparoscopic surgery after the preoperative chemotherapy (CDDP 4 course). On preoperative 3D-CT simulation, the positional relationship between the lesion, vasculature and bile duct had been described well. And the laparoscopic tumor resection (partial hepatectomy) was safely performed. Case 2: 11 m female with Congenital Cystic Adenomatoid Malformation (CCAM) underwent thoracoscopy-assisted lobectomy. On preoperative 3D-CT simulation, the positional relation ship between the lesion, vasculature and bronchus had been described. Furthermore, 3D-CT described the aberrant-V2 which was arisen from inferior pulmonary vein to drain the right upper lobe. And the thoracoscopy-assisted resection of right upper lobe was safely performed. Case 3: 6-years-old male with mediastinal cyst (e.g. bronchogenic cyst) underwent completely-thoracoscopic tumorectomy. On preoperative 3D-CT simulation, the positional relationship among the lesion, bronchi, cardiovascular system, and esophagus. Conclusions: Preoperative 3D-CT simulation and intraoperative navigation for pediatric minimally invasive surgery were useful and feasible. Keywords: Hepatoblastoma, CCAM, Mediastinal cystic tumor